2000
DOI: 10.1097/00004694-200001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The evaluation and management of acute spondylolysis remains unclear in part because of outcome data that are primarily subjective. The aim of this study was to evaluate and monitor these patients objectively using quantitative single-photon emission computed tomography (SPECT). Thirty-four patients were so observed clinically between 1987 and 1996 and were studied with an initial and at least one follow-up SPECT scintigram. Initial radiographs and planar bone scans failed to demonstrate the pars lesion in 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, a retrospective study of a cohort of adolescents (mean age 13.9 ± 2.2 years) with symptomatic baseball participation was identified as the fourth most common sport identified, 8.9% of the patients being identified as baseball players, within the cohort of patients with spondylolysis (Ladenhauf et al, 2013). In other studies referenced by Ladenhauf et al, LBP frequency occurred in between 8.5% and 14.6% of youth baseball players (ages 12–15.5; Anderson, Sarwark, Conway, Logue, & Schafer, 2000; Blanda, Bethem, Moats, & Lew, 1993; Miller, Congeni, & Swanson, 2004). …”
Section: Association Of Lbp In Individuals With Baseball Playing Historymentioning
confidence: 78%
“…However, a retrospective study of a cohort of adolescents (mean age 13.9 ± 2.2 years) with symptomatic baseball participation was identified as the fourth most common sport identified, 8.9% of the patients being identified as baseball players, within the cohort of patients with spondylolysis (Ladenhauf et al, 2013). In other studies referenced by Ladenhauf et al, LBP frequency occurred in between 8.5% and 14.6% of youth baseball players (ages 12–15.5; Anderson, Sarwark, Conway, Logue, & Schafer, 2000; Blanda, Bethem, Moats, & Lew, 1993; Miller, Congeni, & Swanson, 2004). …”
Section: Association Of Lbp In Individuals With Baseball Playing Historymentioning
confidence: 78%
“…Bone scanning in shoulders has been used to detect frozen shoulder,7,18,19) osteolysis of the distal clavicle,20,12) pseudoarthrosis of the acromion,21) os acromiale,22) traction apophysitis of the acromion,23) and rotator cuff disease 7,18)…”
Section: Discussionmentioning
confidence: 99%
“…A bone scan, which is an aff ordable diagnostic tool for analyzing shoulder pain, is highly versatile and it provides high-quality medical images. When using SPECT with a bone scan, a phosphoric acid-based combination was found to increase the uptake at the spots where the bone metabolism is enhanced, and this makes it possible to obtain an early diagnosis before impingement syndrome directly affects the shoulder bones 6,7). SPECT bone scintigraphy is also more sensitive than planar imaging because it is possible to separate the underlying and overlying distributions of activity into sequential tomographic images 6)…”
mentioning
confidence: 99%
“…In recalcitrant cases, electrical stimulation may be added [9,27,28]. Prompt treatment of patients with early pars stress has been shown to result in more predictable symptom relief and less likelihood of progression to spondylolisthesis [29-31]. Surgery is reserved for patients who do not respond to conservative management (approximately 5%), have progressive spondylolisthesis, intractable pain or neurological deficits [18].…”
Section: The Diagnosis and Treatment Of Spondylolysismentioning
confidence: 99%
“…Studies have consistently demonstrated that SPECT is more sensitive than planar bone scintigraphy to identify skeletal lesions [31-33]. Collier et al compared planar bone scintigraphy and SPECT in 19 adults with radiographic evidence of spondylolysis and/or spondylolisthesis and found that SPECT was more sensitive in identifying sites of "painful" pars interarticularis defects and that SPECT allowed more accurate localization of the defect [19].…”
Section: The Utility Of Spect Over Planar Bone Scintigraphy In the Evmentioning
confidence: 99%